PERANCANGAN TAMAN KECAMATAN DI DESA SUNGAI RADAK II KECAMATAN TERENTANG KABUPATEN KUBU RAYA - Sekar, Sekar; Purnomo, Yudi; Zain, Zairin (JMARS: Jurnal Mosaik Arsitektur, 2026)
A sub-district park is a park intended to serve the residents of one sub-district. Parks are public open areas that function as social and aesthetic spaces for ecological, recreational, educational or other activities at the sub-district level. In an effort to design recreational facilities, as well as becoming a tourist attraction for the people of Terentang District, where there is no recreation area in the area, so that it can be realized as the main recreation place for the people of Terentang District. Based on the description above, the people of Terentang District need a recreational facility that has an educational function so that it can provide benefits. Based on the needs of the community, it is necessary to consider designing a "District Park in Sungai Radak II Village, Terentang District, Kab. Kubu Raya”, a recreational facility that can provide facilities and infrastructure for the community. Park visitors are divided into 4 age groups: children, teenagers, adults and the elderly. The space is spacious but still safe for children and elderly visitors. So it can provide visitor comfort. The sub-district park design has recreational and educational facilities such as arts performance areas, playgrounds, sports areas, reading areas, on same design site.